Microstructure and magnetic properties of FePt-(C, SiO2) granular films deposited on MgO, MgTiO, and MgTiON underlayers. (December 2018) - Sepehri-Amin, H.; Nagano, Miho; Seki, T.; Ho, H.; Tripathy, D.; Pirzada, S.; Srinivasan, K.; Yuan, H.; Dorsey, P.; Ajan, A.; Hono, K.
Abstract: We investigated the microstructure and magnetic properties of FePt-(C, SiO2 ) granular films deposited on MgO, MgTiO, and MgTiON underlayers. The coercivity and grain size of the FePt-(C, SiO2 ) film are substantially degraded when deposited on the MgTiO underlayer compared to those on the MgO underlayer, while they become comparable when deposited on the MgTiON underlayer. Atomic resolution STEM-EDS showed Ti in the MgTiO underlayer diffuses into FePt grains, while it is suppressed using the MgTiON underlayer. This suggests that MgTiON is a good choice for a conductive underlayer for growing L10 -FePt perpendicular recording media for heat assisted magnetic recording. Graphical abstract: Unlabelled Image